THE STYLE OF LANGUAGE IN 5SOS SONGS: VOODOO DOLLS AND INVISIBLE - Berya Kamayan Adi Martinus; Nova Noor Aisyah (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This study aims to describe the figurative language and idioms which include the meaning of the figurative language and idioms that used by 5SOS on their songs: Voodoo Dolls and Invisible. To analyze the data, the stylistics approach that focuses on the lexical level of stylistics is used here. The lexical level is used to analyze the figurative language and the lexical meaning, while the theory that used in this study is following the Targian’s theory to consider the figurative language in the data. The second purposes of this study, is to understand the lexical meaning which using the theory of Chaer. Meanwhile, Parera’s theory about that there are three procedures to find the elements of the meaning of words as follows is also used here. As the result of this study, the language style of 5SOS by analyzing the data are describing youth problems, but not all of the figurative language elements as in Tarigan theory is contained in both of the song lyrics.